2022
DOI: 10.1038/s41467-022-35358-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulating glycosphingolipid metabolism and autophagy improves outcomes in pre-clinical models of myeloma bone disease

Abstract: Patients with multiple myeloma, an incurable malignancy of plasma cells, frequently develop osteolytic bone lesions that severely impact quality of life and clinical outcomes. Eliglustat, a U.S. Food and Drug Administration-approved glucosylceramide synthase inhibitor, reduced osteoclast-driven bone loss in preclinical in vivo models of myeloma. In combination with zoledronic acid, a bisphosphonate that treats myeloma bone disease, eliglustat provided further protection from bone loss. Autophagic degradation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Glycosphingolipid is a bioactive lipid that mediate key processes such as apoptosis and autophagy. Leng et al reported that eliglustat could specifically block the synthesis of glycosphingolipid and autophagic degradation of TRAF3 to reduce osteoclastogenesis [ 27 ]. Furthermore, other metabolic process including the synthesis of cellular nitrogen compound, lysine [ 28 ] and choline [ 29 ] were also associated with autophagy [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glycosphingolipid is a bioactive lipid that mediate key processes such as apoptosis and autophagy. Leng et al reported that eliglustat could specifically block the synthesis of glycosphingolipid and autophagic degradation of TRAF3 to reduce osteoclastogenesis [ 27 ]. Furthermore, other metabolic process including the synthesis of cellular nitrogen compound, lysine [ 28 ] and choline [ 29 ] were also associated with autophagy [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of GSL synthesis using NB-DNJ, a selective GCS inhibitor, dramatically inhibited RANKL-induced osteoclastogenesis [ 135 ]. Elegant preclinical studies demonstrated that Eliglustat, an FDA-approved small GSL synthetic inhibitor used for the treatment of Gaucher disease type 1 in adults [ 136 ], was capable to reduce osteoclast-driven bone loss in MGUS and MM models, acting as autophagy inhibitor which prevents TRAF3 degradation through a GLS-dependent mechanism [ 137 ].…”
Section: Lipid Metabolic Vulnerabilities Of MMmentioning
confidence: 99%
“…Glycosphingolipids located outside the cell membrane are important in cell adhesion, cell-cell interactions, and oncogenesis. In MM and MGUS preclinical models, it was shown that Eliglustat can inhibit autophagy through the glycosphingolipid mechanism, thereby maintaining osteoclastogenesis and preventing bone loss [ 169 ] . The tumor burden-reducing effect of the combination of hexokinase-2 inhibitor 3-bromopyruvate and Bortezomib was published [ 87 ] .…”
Section: Therapeutics For Autophagy In MMmentioning
confidence: 99%
“…Furthermore, the combination of 3-methyladenine and VEGF inhibitor Bevacizumab in MM cells promoted apoptosis [133] . In a recent study, NVP-BEZ235 was discovered to induce autophagy through the mTOR2-Akt-FOXO3a-BNIP3 signaling pathway in MM cell lines, mouse models, and primary samples [168] . Targeting the PI3K/AKT/mTOR signaling pathway, which is central to cell life and death choices, is a good strategy and a powerful therapeutic option for clinicians.…”
Section: Pi3k/akt/mtor Inhibitorsmentioning
confidence: 99%